Perbandingan Metode Index Card (Table) Match dan Timeline dalam Peningkatan Hasil Belajar Mahasiswa pada Pembelajaran Sejarah Kebudayaan Islam - Ahmad Zubaidi (Islamic University of Indonesia, 2021)
The problems of learning the history of Islamic culture that occur include the perception of students who regard it as boring learning and too many perspectives from references that exist in the history of Islamic culture itself. On the other hand, educators are required to apply learning methods that are fun and not boring and require students to think more critically about the learning to be carried out. This study aims to see whether there are differences that occur in the index card (table) match and timeline learning methods in improving student learning outcomes in the history of Islamic culture students and if there are differences which learning outcomes are higher than the application of the two methods. The research method used is an experimental study whose population is all 6th semester students at PAI UII in the 2020/2021 academic year in the Islamic Cultural History course class A, B, C, and D and classes A and C were selected to be the sample which class A is the control class with the index card (table) match method and class C is the experimental class with the timeline method. The results of this study stated that there was a difference between the 2 (two) classes before and after treatment, with each experimental class of 28.45 the increase value compared to the control class of 23.89. This indicates that the experimental class has a higher improvement than the control class.Keywords:Â Index Card (Table) Match Method; Timeline Method, History of Islamic Culture